A Bone Anabolic Effect of RANKL in a Murine Model of Osteoporosis Mediated Through FoxP3+ CD8 T Cells. (21st May 2015) - Buchwald, Zachary S; Yang, Chang; Nellore, Suman; Shashkova, Elena V; Davis, Jennifer L; Cline, Anna; Ko, Je; Novack, Deborah V; DiPaolo, Richard; Aurora, Rajeev
ABSTRACT TNF‐α and IL‐17 secreted by proinflammatory T cells (TEFF) promote bone erosion by activating osteoclasts. We previously demonstrated that in addition to bone resorption, osteoclasts act as antigen‐presenting cells to induce FoxP3 in CD8 T cells (TcREG). The osteoclast‐induced regulatory CD8 T cells limit bone resorption in ovariectomized mice (a murine model of postmenopausal osteoporosis). Here we show that although low‐dose receptor activator of NF‐κB ligand (RANKL) maximally induces TcREG via Notch signaling pathway to limit bone resorption, high‐dose RANKL promotes bone resorption. In vitro, both TNF‐α and IL‐17, cytokines that are abundant in ovariectomized animals, suppress TcREG induction by osteoclasts by repressing Notch ligand expression in osteoclasts, but this effect can be counteracted by addition of RANKL. Ovariectomized mice treated with low‐dose RANKL induced TcREG that suppressed bone resorption, decreased TEFF levels, and increased bone formation. High‐dose RANKL had the expected osteolytic effect. Low‐dose RANKL administration in ovariectomized mice lacking CD8 T cells was also osteolytic, confirming that TcREG mediate this bone anabolic effect. Our results show that although RANKL directly stimulates osteoclasts to resorb bone, it also controls the osteoclasts' ability to induce regulatory T cells, engaging an important negative feedback loop. In addition to the conceivable clinical relevance to treatment of osteoporosis, these observations have potential relevance to induction of tolerance and autoimmune diseases. © 2015 American Society for Bone and Mineral Research.